PRESENTASI DIRI PERSONAL TRAINER GYM DI KOTA PEKANBARU - Yuditia Winanda; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Personal trainer is a professional workforce who has knowledge and expertise in the field of fitness exercises (fitness). To be a good personal trainer especially in the city of Pekanbaru, no doubt personal trainers run a different role with their daily life when not a personal trainer. They try to control themselves, able to manage impression management such as appearance, physical condition, actual behavior and movement, so that their behavior as a personal trainer can be said good and successfully cover their behavior that is not in accordance with the profession personal trainer, which can damage the name Either as a personal trainer. The purpose of the research is to know the life of Front Stage (a front step) of a gym personal trainer in Pekanbaru city and to know the life of the backstage backstage of a personal gym trainer in Pekanbaru city.This research uses qualitative method with phenomenology approach with in-depth interview data collecting technique and observation and validity technique of elongation data of participation and triangulation. Informants in this study amounted to 3 (three) people who work as personal trainers. To test the validity of the data writer used the method of extension of participation and triangulation.The results revealed that the lives of informants as personal trainers on the front stage require them to communicate firmly but friendly and understand the science of fitness and run a healthy lifestyle. They are also demanded to look perfect like a personal trainer. While the life of the informant as a personal trainer on the stage behind the informants more freely show themselves and show the other side of him that is not bound by rules such as smoking, clubbing and steroid use. The self-presentation of the informant as a personal trainer shows the results of the differences between each informant in managing the message and the impression that they want to present rather than presenting themselves on the backside that has a smaller scopeKey words : Personal trainer, Gym, Fitness, Sterodi, Suplement